Changes in land use and land cover as a result of the failure of a mining tailings dam in Mariana, MG, Brazil - Aires, Uilson Ricardo Venâncio; Santos, Bismarck Soares Matos; Coelho, Clívia Dias; Silva, Demetrius David da; Calijuri, Maria Lúcia (Land Use Policy, 2018)
The failure of the mining tailings dam in Mariana, Minas Gerais, Brazil, was the largest disaster of its type in Brazil, generating serious environmental and socioeconomic problems. The aim of this study was to identify potential sites for the disposal of the tailings that accumulated along the watercourses affected by the dam failure in the municipalities of Mariana and Barra Longa, as well as to quantify the area affected by the tailings. To quantify the area affected by the tailings dam failure, the Land Change Modeler (LCM) tool was used to verify the changes in land use and land cover that occurred in the periods before and after the environmental impact. For the identification of the suitable sites for tailings disposal, multicriteria analysis was performed using the Idrisi Selva® software and considering three scenarios to identify potentially affected areas through the application of the weighted linear combination (WLC) and ordered weighted average (OWA) techniques. In scenario 1, the WLC technique was applied, considering average risk and high compensation. In scenarios 2 and 3, the OWA technique was applied, with high risk and high compensation for scenario 2 and low risk and high compensation for scenario 3. The highest suitability value for tailings disposal was identified in scenario 2, which obtained the maximum value of 213 on a scale of 0–255, while for the scenarios 1 and 3, the suitability values were 158 and 124, respectively. The largest site for the tailings dam identified in the analysis for the municipally of Mariana has a size of 0.25 km2 and obtained a suitability value of 207. In the municipally of Barra Longa, the largest site identified has a size of 0.037 km2, with maximum suitability value of 209. In relation to the changes in land use and cover, it was verified that the vegetated areas, composed mainly of riparian forest and pasture, presented greater losses as a consequence of the dam failure, with reductions of 11.99 and 4.81 km2, respectively, demonstrating that the dam rupture disaster has caused serious damage to the environment and the population living in the region.
Keywords: Environmental disaster; Geographic information system; Multicriteria analysis